HELLP syndrome in pregnancy as a cause of sudden unexpected death and spontaneous hepatic rupture: A medico-legal autopsy case report - Kanchana Sujirachato (2018)
This is the first reported medico-legal autopsy case in Thailand. It is a case of a 26-year-old Thai female with primigravida and 34 weeks gestational age that had sudden unexpected death. The laboratory investigations before death revealed evidence of hemolysis, which is decreased hematocrit, elevated lactate dehydrogenase (865 U/L), and low platelet count (8.7 x 10 9 cells/L). These findings were compatible with HELLP (Hemolysis, Elevated Liver enzymes, and Low Platelets) syndrome. The autopsy findings showed two ruptures of the right lobe of the liver, hepatic subcapsular hematoma, rupture of Glisson's capsule, and massive hemoperitoneum with abruptio placentae. Histological features of liver and kidneys revealed specific characteristics that can assist the forensic pathologist to diagnose HELLP syndrome when laboratory examinations are not available.